∫0π2 dx1 + tan3x = ? from Mathem

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

931.

If sin-12x1 + x2dx = fx - log1 + x2 then f(x) is equal to

  • 2xtan-1(x)

  • - 2xtan-1(x)

  • xtan-1(x)

  • - xtan-1(x)


932.

If xa3 - x3dx = g(x) +c, then gx is equal to :

  • 23cos-1x

  • 23sin-1x3a3

  • 23sin-1x3a3

  • 23cos-1xa


933.

If dxx2 + 2x + 2 = fx + c, then f(x) is equal to

  • tan-1x + 1

  • 2tan-1x + 1

  • - tan-1x + 1

  • 3tan-1x + 1


934.

Observe the following statement:

A : x2 - 1x2ex2 + 1x2dx = ex2 + 1x2 + cR : f'xefxdx = fx + c

Then which of the followmg is true ?

  • Both A and R are true and R is not thecorrect reason for A

  • Both A and R are true and R is the correct reason for A

  • A is true, R is false

  • A is false, R is true


Advertisement
935.

Dividing the interval [0, 6] into 6 equal parts and by using trapezoidal rule the value of 06x3dx is approximately

  • 330

  • 331

  • 332

  • 333


Advertisement

936.

0π2 dx1 + tan3x = ?

  • π

  • π2

  • π4

  • 3π2


C.

π4

I =  0π2 dx1 + tan3x I =   0π2 cos3xsin3x + cos3xdx        ...iI =  0π2 cos3π2 - xsin3π2 - x + cos3π2 - xdxI =  0π2 sin3 xsin3x + cos3xdx        ...iiOn adding Eqs. i and ii, we get2I =  0 π2 sin3x + cos3xsin3x + cos3xdx    =   0 π2 1 dx = π2 I = π4


Advertisement
937.

- 11 coshx1 +e2xdx = ?

  • 0

  • 1

  • e2 - 12e

  • e2 + 22e


938.

If ex - 1ex + 1dx = fx + c, then fx is equal to

  • 2logex - 1

  • 2loge2x - 1

  • 2logex + 1 - x

  • 2loge2x + 1


Advertisement
939.

tan-11 - x1 + xdx = ?

  • 12xcos-1x - 1 - x2 +c

  • 12xcos-1x + 1 - x2 +c

  • 12xsin-1x - 1 - x2 +c

  • 12xsin-1x + 1 - x2 +c


940.

sinx + 8cosx4sinx + 6cosxdx = ?

  • x + 12log4sinx + 6cosx + c

  • 2x + log2sinx + 3cosx + c

  • x + log2sinx + 3cosx + c

  • 12log4sinx + 6cosx + c


Advertisement